Memória e resistência na construção das famílias escravas no sul de Minas Gerais (1810-1888) - Correia, Daniel Camurça (2011)
This work aims analyze the construction of slave families in southern Minas Gerais, between the decades from 1810 to 1880. This period is marked by the "urban memory" of the major cities of the baixo Vale do Sapucaí, as exempt of the presence slave, mainly by the benevolence of the agriculturists of that epoch. With plentiful and unpublished ecclesiastical documentation was possible rethink this image. Using marriage, baptism and death certificates, as well as records of correspondence issued and sent by the presidency of the province was located a plurality of family realities, in which the captives were present, living and surviving in the complex web of the reality of south Minas, opening up possibilities for new perspectives on memory and endurance of men, women and children, free or slaves, in slavery times